Experimental Polish-Lithuanian Corpus with the Semantic Annotation Elements - Danuta Roszko; Roman Roszko (Cognitive Studies | Études cognitives, 2015)
Experimental Polish-Lithuanian Corpus with the Semantic Annotation Elements